Liquid biopsy in triple-negative breast cancer: a promising tool for diagnosis, prognosis, and treatment monitoring - Brogna, Marianna Rita; Ferrara, Gerardo; Varone, Valeria; Montone, Angela; Fava, Adriana; Schiano, Maria Rosaria; Del Sesto, Michele; Pizza, Nubia; Prota, Annalisa; Barra, Carmela; Collina, Francesca (Frontiers in Oncology, 2026)
Triple-negative breast cancer (TNBC) is a highly aggressive and heterogeneous subtype of breast cancer, characterized by poor prognosis and limited treatment options. With the advancements in precision oncology, liquid biopsy has emerged as a promising, non-invasive tool for diagnosing TNBC, predicting prognosis, and monitoring treatment response. Circulating tumor DNA (ctDNA) and other biomarkers, such as circulating tumor cells (CTCs), exosomal RNA, and non-coding RNAs, offer valuable insights into tumor heterogeneity, disease progression, and therapeutic efficacy. Recent research has indicated that the presence of ctDNA following neoadjuvant chemotherapy is associated with reduced progression-free survival. Additionally, mutations in key genes such as TP53 and PIK3CA/AKT, along with microRNA alterations (e.g., miR17, miR19a, miR105), have been identified as potential indicators of treatment response and resistance. Furthermore, the study of CTCs enables real-time tumor dissemination profiling, which may enhance prognostic accuracy. Despite these promising developments, significant challenges persist in the standardization and clinical implementation of liquid biopsy techniques. This review provides a comprehensive overview of the current and future applications of liquid biopsy in TNBC management, highlighting its potential to improve early disease detection, optimize therapeutic strategies, and refine patient classification. Integrating liquid biopsy into routine clinical practice could lead to better treatment outcomes and more personalized approaches to TNBC care.